Analisis Tingkat Kesejahteraan Petani Lada Di Kawasan Perbatasan Entikong Kalimantan Barat - Pebrianti, Pebrianti; Suyatno, Adi; Komariyati, Komariyati (Fakultas Pertanian Universitas Tanjungpura, 2025)
Analysis Of The Welfare Level Of Pepper Farmers In The Entikong Border Area Of West Kalimantan. The strategic border area opens up opportunities for market access. The opening of market access in the Entikong Border Area affects the economy of the people who depend on the production of pepper commodities. This research aims to determine the level of welfare of pepper farmers in the Entikong Border Area, West Kalimantan. The methods used in this research are qualitative and quantitative with a descriptive approach. The selection of places is done intentionally (Purposive), namely in the Entikong Border Area with the consideration that this location is the largest pepper producing area in Sanggau Regency, besides the selection of locations based on many farmers who cultivate pepper. Based on the results of data analysis using BPS criteria, in this study the output results show that the welfare level of pepper farmers in the Entikong Border Area is included in the category of moderate welfare level.